Haiti : Diagnostic and Proposals for Agriculture and Rural Development Policies and Strategies - World Bank (Washington, DC, 2012)
The overall objective of the present study is to contribute to the knowledge-base that is urgently required for the implementation of sustainable rural development activities in Haiti. The study concentrated on the following two objectives: update knowledge and produce a series of maps of regional physical socio-economic and institutional characteristics of the rural sector at a reasonable level of spatial disaggregation to improve targeting of future interventions; and test and build consensus around specific priority recommendations of the Interim Cooperation Framework with respect to the regional dimension of growth and poverty alleviation. The study follows a dual path of interest in both poverty alleviation as well as economic growth potential. It is widely recognized that in countries like Haiti with engrained and widespread inequality, it is often impossible to abate poverty through growth strategies exclusively. To be realistic, therefore, policy and investment responses to rural needs have to support households' intrinsic strategies for getting out of poverty.